PRACTICE-ORIENTED COURSE ON ENGINEERING PEDAGOGY: DEVELOPMENT OF SOCIAL COMPETENCE - I. V. EDNERAL; R. Z. SAFIEVA (Высшее образование в России)
This article highlights the practice of teaching Humanities to technical students of different training levels (from undergraduate to postgraduate students). Program of each level and every subject include both reduced theoretical basis and practical training. The paper considers the samples of the programs, practical tasks and principles of their selection. The chair of engineering pedagogy of Gubkin Russian State University of Oil and Gas now works out a set of pedagogical and psychological programs such as “Psychology and Pedagogy”, “Psychology of student teams”, “Pedagogical Ethics”, and “Pedagogical Rhetoric” that provide a basis for development of students’ social skills. The consistency in the organization of the practical training as well as theoretical background promote development of students’ social competence, self-confidence both in professional activities and in other life situations. The latter is particularly important for postgraduate students as far as they make up the main teaching reserve of every university.